Australian consensus statements for the regulation, production and use of faecal microbiota transplantation in clinical practice. Issue 5 (11th February 2020) - Haifer, Craig; Kelly, Colleen R; Paramsothy, Sudarshan; Andresen, David; Papanicolas, Lito E; McKew, Genevieve L; Borody, Thomas J; Kamm, Michael; Costello, Samuel P; Andrews, Jane M; Begun, Jakob; Chan, Hiu Tat; et al.
Abstract : Objective: Faecal microbiota transplantation (FMT) has proved to be an extremely effective treatment for recurrent Clostridioides difficile infection, and there is interest in its potential application in other gastrointestinal and systemic diseases. However, the recent death and episode of septicaemia following FMT highlights the need for further appraisal and guidelines on donor evaluation, production standards, treatment facilities and acceptable clinical indications. Design: For these consensus statements, a 24-member multidisciplinary working group voted online and then convened in-person, using a modified Delphi approach to formulate and refine a series of recommendations based on best evidence and expert opinion. Invitations to participate were directed to Australian experts, with an international delegate assisting the development. The following issues regarding the use of FMT in clinical practice were addressed: donor selection and screening, clinical indications, requirements of FMT centres and future directions. Evidence was rated using the GRADE (Grading of Recommendations Assessment, Development and Evaluation) system. Results: Consensus was reached on 27 statements to provide guidance on best practice in FMT. These include: (1) minimum standards for donor screening with recommended clinical selection criteria, blood and stool testing; (2) accepted routes of administration; (3) clinical indications; (4) minimum standards for FMT production and requirements for treatment facilities acknowledging distinction between single-site centres (eg, hospital-based) and stool banks; and (5) recommendations on future research and product development. Conclusions: These FMT consensus statements provide comprehensive recommendations around the production and use of FMT in clinical practice with relevance to clinicians, researchers and policy makers.